Impact of NCT Dream's Endorsement and Parasocial Interaction in Driving Purchase Decisions via Brand Awareness - Mahendri, Wisnu; Rahmah , Madinah Nur Aliyah (Business Management Research, 2026)
This study aims to examine the influence of Brand Ambassador, in this case NCT Dream, and Parasocial Interaction on the purchasing decision of Tos Tos Tortilla Chips through the mediation of Brand Awareness. In the marketing context, Brand Ambassador serves to introduce and build brand image in the minds of consumers, while parasocial interaction deepens the emotional closeness between fans and idols, which can influence purchasing behavior. Data were collected through a survey involving 150 respondents who are NCT Dream fans and consumers of Tos Tos products. The results of the analysis using Structural Equation Modeling (SEM) show that Brand Ambassador and Parasocial Interaction have a positive and significant effect on Brand Awareness. Brand Awareness itself has a significant influence on purchasing decisions. Although Brand Ambassador does not have a direct effect on purchasing decisions, its influence can be felt through increased Brand Awareness which then drives purchasing decisions. Conversely, Parasocial Interaction has a direct and indirect effect on purchasing decisions through Brand Awareness. These findings provide insight that celebrity influence in marketing, especially through parasocial interaction, plays an important role in building brand awareness which ultimately influences consumer purchasing decisions.